Enlightening Pharmacological Mechanisms of Cannabidiol in Epilepsy: A Comprehensive Review on their Neuroprotective Potential - Shrivastava, Aman; Gupta, Jeetendra Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Cannabinoids interact with Cannabinoid Receptors (CBRs) and some related non-cannabinoid transcription factors within neurological and non-neuronal-specific receptors. The current review has covered pharmacological molecular mechanisms during an epileptic attack and provided a beneficial therapeutic approach for the treatment of neurological disorders. CBRs and new targets may be involved in Cannabidiol (CBD) effects. Although it has a low affinity for both CB1 and CB2 receptors, CBD can effectively block CB1 receptors when concentrations are high. The following are numerous potential CBD goals: (A) Blocking GPR55 receptors; (B) Systematic desensitization of TRPV1 channels; (C) Suppressing adenosine re-uptake transporters; (D) Regulating GABA production; and (E) Influencing the Endocannabinoid networks. According to the current review, numerous outstanding cannabis formulations are currently being developed and proven in numerous clinical studies. Nevertheless, more research is urgently needed to determine the best dosage and proportions of cannabinoids for reducing seizure frequency. This study needs to take place in huge, rising randomized clinical trials that really can reveal the rewards and drawbacks of cannabinoids in controlled patients. Furthermore, there is a lot of significant variation in the experimental approaches performed, particularly when it comes to the length of immunosuppressive drugs, dosages, and delivery methods in animal models. So, reproducing the existing results using comparable methods will be one of the biggest challenges in the additional investigation
Keywords: Cannabinoids; Epilepsy; Experimental Models; Preclinical Study; Pharmacological; Mechanism; Neuroprotective Potential